2015
DOI: 10.1016/j.joca.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Knee extensor muscle weakness is a risk factor for development of knee osteoarthritis. A systematic review and meta-analysis

Abstract: The objective of this study was to perform a systematic review and meta-analysis on the association between knee extensor muscle weakness and the risk of developing knee osteoarthritis. A systematic review and meta-analysis was conducted with literature searches in Medline, SPORTDiscus, EMBASE, CINAHL, and AMED. Eligible studies had to include participants with no radiographic or symptomatic knee osteoarthritis at baseline; have a follow-up time of a minimum of 2 years, and include a measure of knee extensor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
246
1
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(260 citation statements)
references
References 30 publications
3
246
1
10
Order By: Relevance
“…Our data extends previous reports showing a significant increase in the number of subjects with OA following a combined injury (concurrent meniscus and/or cartilage lesions) compared to those with isolated ACL injury. Concurrent and/or subsequent additional injuries, particularly meniscal injuries, seem to drive post-traumatic OA development and progression The meniscus should therefore be preserved whenever possible 32,49,51 and treatment strategies for patients with knee OA is exercises such as quadriceps muscle strengthening and aerobic exercises, as well as normalizing body weight for those who are overweight or obese 34,39 . While the prevalence of radiographic OA reported in the current study is in line with previous reviews 8,35 , there is a large variation in the reported prevalence of TF and PF OA after ACLR (10-90%) 8,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data extends previous reports showing a significant increase in the number of subjects with OA following a combined injury (concurrent meniscus and/or cartilage lesions) compared to those with isolated ACL injury. Concurrent and/or subsequent additional injuries, particularly meniscal injuries, seem to drive post-traumatic OA development and progression The meniscus should therefore be preserved whenever possible 32,49,51 and treatment strategies for patients with knee OA is exercises such as quadriceps muscle strengthening and aerobic exercises, as well as normalizing body weight for those who are overweight or obese 34,39 . While the prevalence of radiographic OA reported in the current study is in line with previous reviews 8,35 , there is a large variation in the reported prevalence of TF and PF OA after ACLR (10-90%) 8,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent systematic review identified knee extensor weakness as a risk factor for the development of knee OA. 32 No review, however, has yet investigated the association between hip strength and development of knee OA. Compiling evidence of hip strength deficits and their association with the development of symptomatic knee OA may help to generate strategies to prevent knee OA development and progression.…”
Section: T T Conclusionmentioning
confidence: 99%
“…The meta-analysis showed that knee extensor muscle weakness was associated with an increased risk of developing knee OA (Fig. 21) [66]. Although the role of knee extensor muscle weakness as a risk factor for the development of knee OA is not fully understood, the knee extensors work as shock absorbers and stabilizers, and hence protect the joint surfaces during loading and movement.…”
Section: Jkommentioning
confidence: 99%
“…The hallmark of illness in OA is joint pain Fig. 21 Results of meta-analyses on knee extensor muscle weakness and the risk of knee OA [66] significantly increased in comparison with the same grade group without knee pain. uCTX-II, another cartilage degradation marker, in K/L grade 2 patients with knee pain was significantly increased in comparison with those in K/L grade 2 without knee pain.…”
Section: Jkommentioning
confidence: 99%